(untitled) (Open Herald: Periodical of Methodical Research, 2026)
This article examines the translation of political speeches using Franklin D. Roosevelt’s Fireside Chat as an example. The study analyzes the structure of the speech, which follows the pattern of problem, crisis explanation, and solution. Special attention is given to the translation of metaphors, everyday expressions, and other stylistic features. The analysis shows that preserving the simple and conversational tone of the original speech is important for achieving an effective translation